The Effectiveness of Mirror Therapy on Muscle Strength Rehabilitation in Non-Haemorrhagic Stroke Patients: Literature Review - Barbosa, Adirson; Septianingrum, Yurike (Journal of Applied Nursing and Health, 2024)
Background: Stroke remains one of the significant problems of long-term disability. Most stroke patients have difficulty performing daily activities due to paresis of the upper limbs, resulting in impaired activities of daily living (ADL) and decreased quality of life. The purpose of this literature review is to find out the Application of Mirror Therapy to Muscle Strength Rehabilitation in non-homorrhagic stroke Patients. Methods: The method used is literature review (PRISMA) using journal databases from PubMed, Science Direct, and Google Scholar in the range 2020-2024 with the keywords "Mirror Therapy", "Muscle Strength Rehabilitation," and "Non-Hemorrhagic Stroke" and stroke obtained as many as 1276 articles. Results: The search for articles according to the criteria and obtained 9 articles that are ready to be reviewed. These articles explain the application of mirror therapy to muscle strength rehabilitation in non-hemorrhagic stroke patients. Conclusion: It is hoped that patients with stroke will endeavor to control mirror therapy.